Utilizing Plastic Waste as a Source of Creativity in Ecobrick Training in Purana Village - Cahyaning Suci, Afita; Syaefudin, Arief; Ainia Mufiatun Nafisah, Dewi; Hanifah, Lutfiah; Mufrodah, Naili; Nalim, Nalim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The current situation regarding plastic waste production presents a formidable challenge that society grapples with daily. The pervasive use of plastic has become nearly inescapable, infiltrating every aspect of our lives, from packaging to consumer goods. This escalating reliance on plastic exacerbates environmental pollution and significantly threatens the ecological balance. The longevity of plastic waste is alarming; it can take hundreds of years to decompose naturally, accumulating vast amounts of waste in landfills and natural habitats. Furthermore, the polymers in plastic are porous, contributing to the gradual increase in air temperatures as they trap heat, further intensifying the global climate change crisis. In response to this pressing issue, the KKN Team Batch 56 Group 33 from UIN K.H. Abdurrahman Wahid Pekalongan initiated a proactive approach by organizing ecobrick training sessions to transform plastic waste into a medium for creativity within Purana Village. This innovative program employed a multifaceted methodology, including socialization to raise awareness, interactive question-and-answer sessions to engage the community, and hands-on training to equip participants with the necessary skills to create eco-bricks. These eco-bricks serve as a practical solution for repurposing plastic waste and as a means to foster community spirit and environmental consciousness. The culmination of this initiative resulted in heightened awareness among community members regarding the significance of creatively utilizing plastic waste. The project's tangible outcome was installing eco-bricks in Kampung Baru Hamlet, transforming them into decorative elements that enhance the streetscape while simultaneously serving as a poignant reminder of the potential for waste to be repurposed. This initiative addresses the immediate concerns surrounding plastic waste and inspires a broader movement towards sustainable practices within the community, ultimately contributing to a cleaner and more environmentally responsible future.